Collagen Organization Within the Cartilage of Trpv4−/− Mice Studied with Two‐Photon Microscopy and Polarized Second Harmonic Generation. Issue 5 (11th October 2019) - Servin‐Vences, M. Rocio; Poole, Kate; Sporbert, Anje; Lewin, Gary R.; Margineanu, Anca
Abstract: The polymodal channel TRPV4 has been shown to regulate development and maintenance of cartilage. Here we investigate whether TRPV4 activity regulates the early deposition and structure of collagen matrix in the femoral head cartilage by comparing the 3D morphology and the sub‐micrometer organization of the collagen matrix between wild type and Trpv4 −/− mice pups four to five days old. Two‐photon microscopy can be used to conduct label‐free imaging of cartilage, as collagen generates a second harmonic signal (second harmonic generation [SHG]) under pulsed infrared excitation. In one set of measurements, we use circularly polarized laser light to reconstruct the 3D morphology of the femoral head cartilage and to measure the tissue thickness. Second, by rotating the direction of the linearly polarized light and using polarized SHG detection, we investigate the sub‐micrometer orientation of collagen fibers in the cartilage. At this developmental stage, we cannot detect statistically significant differences between the two mice strains, although a tendency toward a more random orientation of collagen fibers and a higher thickness of the whole cartilage seems to characterize the Trpv4 −/− mice. We discuss possible reasons for these observations. © 2019 The Authors. Cytometry Part A published by Wiley Periodicals, Inc. on behalf of International Society for Advancement of Cytometry. Abstract : A composition of seven color‐coded polarization images of a cartilage area covering the mouse femoral head. Label‐free imaging is based on the intrinsic property of the collagen fibers composing the cartilage to generate second harmonic signal (second harmonic generation [SHG]) under two‐photon excitation. The polarization images have been acquired by rotating the excitation direction of the linearly polarized laser (red arrow) and detecting the SHG signal along the parallel and perpendicular directions. They reflect the orientation of the fibers relative to the detection parallel to the laser direction: when the fibers emit along the parallel direction, they are represented in red; when the emission is higher on the perpendicular direction, blue and dark blue colors dominate.